Highly compromised auditory spatial perception in aided congenitally hearing-impaired and rapid improvement with tactile technology - Adi Snir; Katarzyna Cieśla; Rotem Vekslar; Amir Amedi (iScience, 2024)
Summary: Spatial understanding is a multisensory construct while hearing is the only natural sense enabling the simultaneous perception of the entire 3D space. To test whether such spatial understanding is dependent on auditory experience, we study congenitally hearing-impaired users of assistive devices. We apply an in-house technology, which, inspired by the auditory system, performs intensity-weighting to represent external spatial positions and motion on the fingertips. We see highly impaired auditory spatial capabilities for tracking moving sources, which based on the “critical periods” theory emphasizes the role of nature in sensory development. Meanwhile, for tactile and audio-tactile spatial motion perception, the hearing-impaired show performance similar to typically hearing individuals. The immediate availability of 360° external space representation through touch, despite the lack of such experience during the lifetime, points to the significant role of nurture in spatial perception development, and to its amodal character. The findings show promise toward advancing multisensory solutions for rehabilitation.